2007
DOI: 10.1080/01421590601045007
|View full text |Cite
|
Sign up to set email alerts
|

Different outcomes of active and reflective students in problem-based learning

Abstract: Background: In the recent past, many medical schools have adopted the problem-based learning (PBL) method in their curriculum. Aim: The key in this type of learning is the small group, which encourages students to perform and, thus, to learn effectively. This means the students must be grouped in such a way for the small group to facilitate the achievement of a better learning outcome. Methods: Using Felder's Learning Inventory, three groups of students were formed: active, reflective and a control with no par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…The relation between learning style and academic achievement, however, is not that clear. Some studies found that students who favoured abstract thinking outperformed those who preferred concrete thinking in the science disciplines (Davies, Rutledge & Davies, 1997), and that reflective students were better in problem solving than active students (Hur & Kim, 2007). Despite this, many more studies disapproved the correlation between learning styles and academic performance (Demirkan & Demirbaş, 2010;Fleming et al, 2011;Gurpinar et al, 2010;Hsieh, Mache, & Knudson, 2012;Wilkinson, Boohan, & Stevenson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The relation between learning style and academic achievement, however, is not that clear. Some studies found that students who favoured abstract thinking outperformed those who preferred concrete thinking in the science disciplines (Davies, Rutledge & Davies, 1997), and that reflective students were better in problem solving than active students (Hur & Kim, 2007). Despite this, many more studies disapproved the correlation between learning styles and academic performance (Demirkan & Demirbaş, 2010;Fleming et al, 2011;Gurpinar et al, 2010;Hsieh, Mache, & Knudson, 2012;Wilkinson, Boohan, & Stevenson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some examples for this type of study are those showing how dysfunctional groups, tutors or even the age or learning type of PBL students influence the group process and learning results (Houlden et al 2001;Hur and Kim 2007). The same holds true for the way students experience their (new) learning environment and their previous experience with learning that will also strongly influence the way they can work with PBL (Albanese 2000) and the resulting learning success (Gijbels et al 2006).…”
mentioning
confidence: 92%
“…Above all the "T" (technology) in STEM is a powerful integrator capable of bringing the component disciplines (science, engineering and mathematics) together for enhanced teaching and learning opportunities (Kumar, 2015a). For example, as Hatch and Brenner (2011) pointed out often "in the U.S. education [system], the "E" in STEM (science, technology, engineering, and math) has been virtually silent" (p. 291). It could be argued that such issues of inadequate integration in designing learning environments be resolved by proper use of interactive technology to integrate the STEM disciplines.…”
Section: Why Problem Based Learning (Pbl)?mentioning
confidence: 99%